Ubiquitin in the peroxisomal protein import pathway - Francisco, T (2014)
PEX5 is the shuttling receptor for newly synthesized peroxisomal matrix proteins. Alone, or with the help of an adaptor protein, this receptor binds peroxisomal matrix proteins in the cytosol and transports them to the peroxisomal membrane docking/translocation module (DTM). The interaction between cargo-loaded PEX5 and the DTM ultimately results in its insertion into the DTM with the concomitant translocation of the cargo protein across the organelle membrane. PEX5 is not consumed in this event; rather it is dislocated back into the cytosol so that it can promote additional rounds of protein transportation. Remarkably, the data collected in recent years indicate that dislocation is preceded by monoubiquitination of PEX5 at a conserved cysteine residue. This mandatory modification is not the only type of ubiquitination occurring at the DTM. Indeed, several findings suggest that defective receptors jamming the DTM are polyubiquitinated and targeted to the proteasome for degradation.